Growth and Content of Seaweed Carrageenan Kappaphycus alvarezii Cultivated at Bottom-off method - Devi Suryani Putri; Nunik Cokrowati; Dewi Putri Lestari; Ahmad Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Kappaphycus alvarezii is a red alga that produces kappa-carrageenan which can be used as raw material for processed foods, medicines, cosmetics, and bacterial media materials. The production of K. alvarezii is increasingly being sought to increase to meet consumer demands. This study aimed to analyse the growth rate and content of carrageenan in K. alvarezii cultivated using the bottom-off method. This research was conducted at the Seaweed Center of Balai Perikanan Budidaya Laut (BPBL), Gerupuk, Pujut District, Central Lombok Regency, West Nusa Tenggara Province. The research method used was experimental with a completely randomized design consisting of five spacing treatments. The treatments in this study were P0 (distance 15 cm as control), P1 (distance 10 cm), P2 (distance 15 cm), P3 (distance 20 cm), P4 (distance 25 cm). K. alvarezii cultivation was carried out for 40 days. The result of this study is the highest yield of carrageenan was obtained at P4 of 6.846%. The highest absolute weight of K. alvarezii was obtained in treatment P4 (25 cm) which was 121.67 g. The highest specific growth was found at P4 (25 cm) which was 1.98%/day. This study concludes that K. alvarezii spacing significantly affects the growth and carrageenan of seaweed cultivated at the bottom-off method.